2016
DOI: 10.2147/ijn.s95301
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of vaginal and rectal herpes simplex virus type 2 transmission in mice: mechanism of antiviral action

Abstract: Topical microbicides to stop sexually transmitted diseases, such as herpes simplex virus type 2 (HSV-2), are urgently needed. The emerging field of nanotechnology offers novel suitable tools for addressing this challenge. Our objective was to study, in vitro and in vivo, antiherpetic effect and antiviral mechanisms of several polyanionic carbosilane dendrimers with anti-HIV-1 activity to establish new potential microbicide candidates against sexually transmitted diseases. Plaque reduction assay on Vero cells p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The specific design and the three-dimensional structure of the G2-S16 dendrimer are essential features to interfere with envelope proteins of HIV-1 or HSV-2 and receptors on the host cells, conferring a multifactorial and nonspecific ability. Many in vitro and in vivo studies confirmed the safety and efficacy of this G2-S16 dendrimer to prevent HSV-2 and HIV-1 infections [17,19]. The G2-S16 dendrimer was stable at various pHs and in the presence of seminal fluids maintaining the anti-HIV-1 activity overtime, this dendrimer did not generate any type of drug resistance and did not cause inflammation or irritation in the vaginal mucosa after administration of G2-S16 dendrimer at various concentrations and different times in female mice and rabbits [17,19,20].…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…The specific design and the three-dimensional structure of the G2-S16 dendrimer are essential features to interfere with envelope proteins of HIV-1 or HSV-2 and receptors on the host cells, conferring a multifactorial and nonspecific ability. Many in vitro and in vivo studies confirmed the safety and efficacy of this G2-S16 dendrimer to prevent HSV-2 and HIV-1 infections [17,19]. The G2-S16 dendrimer was stable at various pHs and in the presence of seminal fluids maintaining the anti-HIV-1 activity overtime, this dendrimer did not generate any type of drug resistance and did not cause inflammation or irritation in the vaginal mucosa after administration of G2-S16 dendrimer at various concentrations and different times in female mice and rabbits [17,19,20].…”
Section: Introductionmentioning
confidence: 87%
“…Many in vitro and in vivo studies confirmed the safety and efficacy of this G2-S16 dendrimer to prevent HSV-2 and HIV-1 infections [17,19]. The G2-S16 dendrimer was stable at various pHs and in the presence of seminal fluids maintaining the anti-HIV-1 activity overtime, this dendrimer did not generate any type of drug resistance and did not cause inflammation or irritation in the vaginal mucosa after administration of G2-S16 dendrimer at various concentrations and different times in female mice and rabbits [17,19,20]. When BALB/c mice or humanize (h)-BLT mice were pre-treated with topical 3% G2-S16 dendrimer and then female vaginally exposed to R5-HIV-1 JR-CSF or HSV-2 333, G2-S16 dendrimer efficiently prevented female vaginal HIV-1 transmission by 84% [19] and HSV-2 by 100% [17].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations